Acoustically generated vorticity in an internal flow - Q., Zhao; P. L., Staab; D. R., Kassoy; K., Kirkkopru (Cambridge University Press (CUP), 2000)
A mathematical model is formulated to describe the initiation and evolution of intense unsteady vorticity in a low Mach number (M), weakly viscous internal flow sustained by mass addition through the sidewall of a long, narrow cylinder. An O(M) axial acoustic velocity disturbance, generated by a prescribed harmonic transient endwall velocity, interacts with the basically inviscid rotational steady injected flow to generate time-dependent vorticity at the sidewall. The steady radial velocity component convects the vorticity into the flow. The axial velocity associated with the vorticity field varies across the cylinder radius and in particular has an instantaneous oscillatory spatial distribution with a characteristic wavelength O(M) smaller than the radius. Weak viscous effects cause the vorticity to diffuse on the small radial length scale as it is convected from the wall toward the axis. The magnitude of the transient vorticity field is larger by O(M−1) than that in the steady flow.An initial-boundary-value formulation is employed to find nonlinear unsteady solutions when a pressure node exists at the downstream exit of the cylinder. The complete velocity consists of a superposition of the steady flow, an acoustic (irrotational) field and the rotational component, all of the same magnitude.
Keywords: Culick steady solution; low-Mach-number weakly viscous internal flow; Asymptotic methods, singular perturbations applied to problems in fluid mechanics; combustion chamber; Hydro- and aero-acoustics; Combustion; unsteady vorticity; asymptotic methods; spatial wave amplitude decay; axial acoustic velocity disturbance; narrow cylinder; acoustic boundary layers; nonlinear axial convection; steady radial velocity field; mass addition